Guillermo Cabrera Infante, for Example - Iwasaki, Fernando (Anales de Literatura Hispanoamericana, 2008)
The article analyses Cuban writer Guillermo Cabrera Infante’s irreverent humour as the basis for the parodic, humoristic and critical currents of Spanish American narrative. Attention is given to the very personal and innovative humour of Tres tristes tigres and to the outstanding virtues, beyond mere wordplay, which led the Cuban to an experimentation unusual in narrative prose but able to affect the very structure of the novel. The qualities of an unclassifiable and innovative genre can be found in all Cabrera Infante’s works.